Amyloid adhesin production in activated sludge is enhanced in lab-scale sequencing batch reactors: Feeding regime impacts microbial community and amyloid distribution. (1st December 2022) - Christiaens, An-Sofie; Van Steenkiste, Manon; Rummens, Koen; Smets, Ilse
Highlights: Thioflavin t revealed enhanced amyloid production in SBRs with different inocula. A more continuous (aerobic) feeding … did not impair bioflocculation. … resulted in a more dispersed distribution of amyloids in sludge flocs. … resulted in a dominance of denitrifiers with amyloid production capacity. Ca. Competibacter and zoogloea were identified as main potential amyloid producers. Abstract: Amyloid adhesins are β-sheet-rich extracellular proteins thought to contribute to bioflocculation. They are present in activated sludge to varying extent. However, it remains unclear which operational conditions promote their production. To this end, the abundance and distribution of amyloids and their potential producers were monitored in two lab-scale reactors operated in sequencing batch mode with an unaerated and aerated reaction phase. Various feeding regimes ranging from feast-famine to nearly continuous feeding were applied. Thioflavin T staining revealed more amyloids in the lab-scale reactors during all operational stages compared to the full-scale industrial and municipal inocula. Furthermore, the feeding regime impacted the distribution of produced amyloids from dense clusters during feast-famine conditions towards a dispersed distribution during nearly continuous feeding. This dispersed presence did not negatively impact the bioflocculation (towards average floc size and shear sensitivity). 16S rRNA sequencing detected several known EPS and amyloid producers. More continuous and, hence, partially aerobic feeding promoted the relative abundance of denitrifiers. Sequential Thioflavin T staining and fluorescence in situ hybridization identified Zoogloea and Ca . Competibacter as potential amyloid producers under the applied conditions. This experiment confirms that amyloid producers need to be triggered for production and that the feeding regime impacts the microbial community composition, which in turn influences the amyloid production and distribution. Graphical abstract: Image, graphical abstract